Ichthyofaunal diversity in Laguna Hule, Costa Rica (UNED Research Journal, 2018)
Laguna Hule is a volcanic origin crater which has been flooded over time, resulting in a deep mass of water with no previous studies about its fish community. For five months we sampled it and a draining stream (Pata de Gallo) with nets, and hook and line. The captured specimens were identified in situ to the possible lowest taxonomic level. The lagoon mostly had species normally found near aquatic vegetation: Amatitlania siquia, Amphilophus alfari, Astyanax aeneus, Cynodonichthys sp., Parachromis dovii, Phallichthys amates and Poecilia gillii (dominant: A. aeneus, P. gillii and P. amates). The stream was dominated by Brachyrhaphis olomina but also had Rhamdia laticauda. The low diversity indices (1,48 in the lagoon and 0,26 in the stream) are characteristic of lacustrine ecosystems. Females were, as expected, larger and more abundant in P. amates and B. olomina; whereas in P. gilli, some males were larger. The area is affected by pollution, introduction of invasive species, uncontrolled fishing and use of destructive fishing gear. We propose demarcation of site protection status and organizing a community group to protect this fish community.
Keywords: Hule lagoon; ichthyology; fish diversity; fresh water fish